Resting state vagal tone in borderline personality disorder: a meta-analysis - Koenig, Julian; Kaess, Michael (Progress in neuro-psychopharmacology & biological psychiatry, 2016)
Borderline personality disorder (BPD) is the most common personality disorder in clinical settings. It is characterized by negative affectivity, emotional liability, anxiety, depression, as well as disinhibition (i.e., impulsivity and risk taking), all of which have been linked to lower resting state vagal tone, which may be indexed by vagally-mediated heart rate variability (vmHRV). Here, we aimed to quantify the current evidence on alterations in resting state vmHRV in individuals with BPD, relative to healthy controls. A rigorous search of the literature, according to the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses”, revealed 5 studies suitable for meta-analysis, reporting vmHRV in individuals with BPD (n=95), relative to healthy controls (n=105). Short-term measures of resting state vmHRV were extracted and subjected to meta-analysis using both random- and fixed effect models in RevMan. BPD displayed lower resting state vmHRV relative to healthy controls in random- (Hedges' g=−0.59, 95% CI [−1.11; −0.06], k=5) and fixed-effect meta-analysis (Hedges' g=−0.56, 95% CI [−0.86; −0.27], k=5). Control for potential publication bias did not change observed findings. Lowered resting state vagal tone may be an important trait characteristic underlying BPD. As prior studies have observed lowered vmHRV in a variety of psychiatric disorders, we propose that lowered vmHRV may reflect a common psychophysiological mechanism underlying difficulties in emotion regulation and impulsivity, in particular.